The Development of Technology-Based Learning Media to Enhance Short Story Reading Interest - Sri Kartini; Yuannisah Aini Nasution; Saprida (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the development of technology-based learning media to enhance students’ interest in reading short stories, addressing the lack of engaging and relevant materials in the learning process. Despite the importance of reading, many students, particularly in grade VIII at SMP Muhammadiyah Rantau Prapat, exhibit low interest in reading short stories. This issue is often linked to the absence of interactive and technology-integrated learning resources. To overcome this challenge, a web-based application was developed, providing interactive short story materials designed to captivate students and improve their reading engagement. The study employs a research and development (R&D) approach using the ADDIE model, which consists of five systematic stages: analysis, design, development, implementation, and evaluation. A total of 30 grade VIII students were randomly selected as research participants. Data collection methods included questionnaires, observations, and statistical analysis to measure the effectiveness of the learning media. The results revealed a significant increase in students’ interest in reading short stories after using the technology-based media. Statistical tests showed that students became more engaged with reading activities, demonstrating a higher level of motivation and comprehension. These findings suggest that integrating technology into reading instruction can be an effective strategy to enhance students’ reading interest and overall engagement in the learning process. The use of interactive elements, such as animations, quizzes, and digital storytelling, contributes to making reading more enjoyable and accessible. This study highlights the need for further exploration of digital learning tools in different educational contexts. Future research should examine the long-term impact of technology-based reading interventions and explore strategies for broader implementation in various schools.